Anabolism, catabolism and proteomic analysis in the slow-twitch muscle of pacu (Piaractus mesopotamicus) submitted to prolonged fasting followed by refeeding - Gabriel Kuniyoshi, Maria Laura [UNESP]; Nunes da Silva-Gomes, Rafaela [UNESP]; Thomazini Zanella, Bruna Tereza [UNESP]; Delazari dos Santos, Lucilene [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Hindawi, 2020)
Here, we aimed to study the slow muscle of the fish Piaractus mesopotamicus submitted to 30 days of fasting (D30) followed by 1 day (D31) or 30 days of refeeding (D60). Histological analysis of fibre diameter was performed in D30 and D60. The gene expression of parvalbumin (pvalb), atrogenes (murf1a, murf1b, mafbx) and anabolic genes (igf-1, mtor) was analysed using RT-qPCR in D30, D31 and D60. The proteome was obtained by shotgun proteomics at D30 and D60, and the set of differentially expressed proteins was analysed by bioinformatics. In all experiments, the control was regularly fed fish. The histological analysis showed no changes in muscle fibre diameter. The expression of catabolic and anabolic genes was not changed, except for the downregulation of igf-1 in D30 and of mafbx in D31. The expression of pvalb was not changed in D30 and D60 but was decreased in D31. The proteomic analysis identified 169 proteins in D30 (24 upregulated and 18 downregulated) and 170 proteins in D60 (17 upregulated and 21 downregulated); many of them were related to energetic metabolism and intracellular Ca2+ homoeostasis. Overall, our results indicate that the slow-twitch muscle presented few changes upon prolonged fasting and refeeding condition.
Keywords: fish; food restriction; proteomics; red muscle; refeeding; slow-twitch fibres